Model Pengembangan Media Pembelajaran Pendidikan Kewarganegaraan Berbasis Aplikasi Augmented Reality Sejarah Proklamasi di STT Indonesia Tanjungpinang - Naufal Muhammad Kautsar; Zulfachmi; Wanhendra (LPPM Sekolah Tinggi Teknologi Indonesia Tanjung Pinang, 2020)
This study aims to: (1) Determine the conditions of learning and teaching activities in Citizenship Education courses prior to the implementation of the development of Android-based learning media. (2) Knowing the development of IT-based learning media in STT Indonesia. The type of research used in this research is research and development research. The data source was chosen by the head of the study program, lecturers of civic education, and 8th semester students at STT Indonesia. This research was conducted in approximately 6 months. This development research resulted in the final product of learning media based on augmented reality of the history of the proclamation. Media development is developed through five stages (analysis, design, development, implementation and evaluation). Based on the results of field trials conducted in small and large classes. The small class trial was carried out in the SI class with a random sample of 5 students, obtaining a result of 82.6%, it was concluded that this product was suitable for use. The results of the extensive trial were carried out to the IF class, SI.KA. The results obtained by 29 IF students got a response with a percentage of 78.2%, it was concluded that this product was feasible to use. Extensive trials conducted on 28 students of SI STT Indonesia Tanjungpinang received a response with a percentage of 74.7%, it was concluded that this product was quite feasible to use. Extensive trials were carried out on 29 students of the STT Indonesia Tanjungpinang KA received a response with a percentage of 87.6%, it was concluded that this product was very suitable for use. Finally, the field trial was carried out on citizenship education lecturers of STT Indonesia Tanjungpinang who received a response with a score of 92, 7%, concluded This product is very feasible to use.